Simulation analysis of the catalytic cracking process of biomass pyrolysis oil with mixed catalysts: Optimization using the simplex lattice design - Chawannat Jaroenkhasemmeesuk (2018)
Copyright © 2018 John Wiley & Sons, Ltd. Bio-oil produced via fast pyrolysis of biomass usually has various undesired properties that can negatively affect its use. Therefore, raw bio-oil needs first to undergo an upgrading stage before it is further used. This paper deals with the study of bio-oil upgrading by means of catalytic cracking with a Y-zeolite/ZSM-5 catalyst, as well as the optimization of the process operating conditions. Several case studies are selected by using the simplex lattice design of experiments, and these are simulated under a range of conditions to study the effect of the key process parameters on the bio-oil conversion. The simulation results show that the catalyst-to-oil ratio is the most influential parameter. An analysis of the obtained data indicates that a Y-zeolite/ZSM-5 catalyst blend with 15.6 to 19.0%wt of Y-zeolite, a catalyst-to-oil ratio in the range of 4.9 to 6.1, a riser height of 24.6 to 30.0 m (residence time ~ 6 s), and a reactor temperature of 350 to 385°C are the preferred conditions that maximize the product conversion, which take values up to 78.5% in the simulations. A comparison against previous experimental results confirms that the value of the ratio between catalyst and bio-oil is a critical design parameter and highlights that the optimum values of the Y-zeolite content and the reactor temperature calculated from the simulation data are in good agreement with those obtained experimentally. The simulation analysis conducted in this study is a suitable tool to investigate the catalytic cracking process for bio-oil upgrading.